A study to explore patterns and factors of depression, anxiety and stress among students preparing for competitive exams in central India - Pachole, Neeti; Thakur, Aditya; Koshta, Harshit; Menon, Manish; Peepre, Kunal (International Journal Of Community Medicine And Public Health, 2023)
Background: Depression, stress and anxiety among students is being increasingly recognized as a major mental health problem. Depression is a common but grave mood disorder. Many chronic mood and anxiety disorders in adults begin as high levels of anxiety in children. Objectives of current study were to explore the level of depression, anxiety and stress and to identify various factors associated with it. Methods: A descriptive, cross-sectional study on 400 students preparing for competitive exams, using a questionnaire having socio demographic profile and DASS 21 scale was carried out. Then data was entered in MS excel and SPSS Software was used for relevant inferential statistical tests of associations. Results: 65.8 % of participants were less than 18 years of age and 57.3 % were males.20.3 % of students were found to be having moderate depression, 8.8 % having severe depression, 17.8 % having moderate anxiety, 27.3% having severe anxiety, 14.8 % having moderate stress, 12 % having severe stress. Stress was found to be significant in females and those having more than 2 siblings. Significant anxiety was found in those having non supportive teachers. Significant depression was found in those having non supportive teachers and parents, those who sleep for less than 6 hours and those spending less than 2 hours on study. Conclusions: Study highlighted common factors leading to depression anxiety and stress among students. Parents and teacher are recommended to develop proper communication and be aware of this problem.